The role of the social construction of the organization with respect to the perception of working conditions and environmental management in four hamlets of an Andean peasant community: Caraz, Ancash - Paredes Tarazona, Mildred (2005)
This research seeks to measure the degree of homogeneity in the perception of working conditions and environmental management, in hamlets of the Cruz de Mayo peasant community: Pampacocha, Queral, Chinchay and Miramar identified for their peculiar organizational social construction; in addition to finding out the relationship between the factors mentioned above. 98 community members participated, out of a total of 546 men and women over 16 years of age; calculated the theoretical sample of 82 at e = 0.1; with a comparison scale with 4 degrees, designed in Spanish and translated into Quechua in the area. Data were obtained in 4 months, with the support of a resident of Queral. Results: According to the data collected, there is a significant relationship at 0.01 between the factors working conditions and environmental management (r = 0.422, Pearson coefficient) with the bivariate correlation. There is a significant relationship between working conditions per farmhouse, at a significance level of 0.019 for ANOVA; and there is no difference due to the significance level of 0.700 of the management of the environment by farmhouse. In conclusion, we point out that: 1) there is a significant relationship between working conditions and environmental management; 2) significant differences are found between the working conditions by farmhouse given the existence of a unique social construction of each farmhouse; 3) there are no differences between the villages in the management of the environment, which is attributed to the social and organizational construction of the community; that is to say, it constitutes a competence of the community, not from the farmhouse.